User Experience of Augmented Reality System for Astronaut's Manual Work Support - Helin, Kaj; Kuula, Timo; Vizzi, Carlo; Karjalainen, Jaakko; Vovk, Alla (Frontiers in robotics and AI, 2018)
This paper introduces Augmented Reality (AR) system to support an astronaut's manual work, it has been developed in two phases. The first phase was developed in Europeans Space Agency's (ESA) project called "EdcAR-Augmented Reality for Assembly, Integration, Testing and Verification, and Operations" and the second phase was developed and evaluated within the Horizon 2020 project "WEKIT-Wearable Experience for Knowledge Intensive Training." The main aim is to create an AR based technological platform for high knowledge manual work support, in the aerospace industry with reasonable user experience. The AR system was designed for the Microsoft HoloLens mixed reality platform, and it was implemented based on a modular architecture. The purpose of the evaluation of the AR system is to prove that reasonable user experience of augmented reality can reduce performance errors while executing a procedure, increase memorability, and improve cost, and time efficiency of the training. The main purpose of the first phase evaluation was to observe and get feedback from the AR system, from user experience point-of-view for the future development. The use case was a filter change in International Space Station (ISS)-Columbus mock-up in the ESA's European Astronaut Centre (EAC). The test group of 14 subjects it included an experienced astronaut, EAC trainers, other EAC personnel, and a student group. The second phase the experiment consisted of an trial and evaluation process. The augmented reality system was tested at ALTEC facilities in Turin, Italy, where 39 participants were performing an actual real astronaut's procedure, the installation of Temporary Stowage Rack (TSR) on a physical mock-up of an ISS module. User experience evaluation was assessed using comprehensive questionnaires, and interviews, gathering an in-depth feedback on their experience with a platform. This focused on technology acceptance, system usability, smart glasses user satisfaction, user interaction satisfaction, and interviews, gathering an in-depth feedback on their experience with a platform. The analysis of the questionnaires and interviews showed that the scores obtained for user experience, usability, user satisfaction, and technology acceptance were near the desired average. Specifically, The System Usability Scale (SUS) score was 68 indicating that the system usability is already nearly acceptable in the augmented reality platform.